Juridical Analysis of Criminal Law Against Acts of Falsification of Health Documents as a Condition of Travel During a Pandemic Covid-19 - Afra Zahra; Kuswardani Kuswardani (LEGAL BRIEF, 2022)
The case of health documents falsification related to the Covid-19 pandemic is a case that must be considered carefully, considering that the health documents falsification has an impact not only on one person but has the potential to endanger many people. The existence of a Covid-19 vaccination certificate and also false negative antigen swab test results can result in more and more virus transmission, given the lack of certainty regarding the condition of the perpetrators. This study is based on a research paper on the principles of law (statute approach) and the concept approach (conceptual approach). Legal material tracing techniques used document study techniques and qualitative analysis of studies. The act of falsifying health documents in the midst of a pandemic is punishable by a maximum of four years in prison. For perpetrators who commit criminal acts in the form of forgery of health documents in digital form can be punished with imprisonment for a maximum of 9 (nine) years and/or a maximum fine of Rp 3,000,000,000.00 (three billion rupiahs). Referring to the provisions of Article 14 of the infectious disease epidemic law, it is known that anyone who deliberately hinders the implementation of epidemic management is threatened with imprisonment for 1 (one) year and/or a fine of up to Rp 1,000,000.00 (One Million rupiahs).